Knight's gambit - Faulkner, William, 1897-1962. (New York : Vintage, 1978)
Contains six mystery stories by twentieth-century American novelist William Faulkner, set in the fictional Yoknapatawpha County, Mississippi, and featuring the character of attorney Gavin Stevens.
Adult
Keywords: Crime -- Mississippi -- Fiction; Crime -- Mississippi -- Fiction; Mystery fiction